Pola Bakteri Aerob pada Sampel Sputum dan Uji Sensitivitas Antibiotik Pasien Rawat Inap di Rumah Sakit Dr. J.H Awaloei - Ribka Milkallah Sepang; Heriyannis Homenta; Fredine E. S. Rares (Jurnal Syntax Admiration, 2025)
Cough with phlegm is the most common medical complaint that leads to referral to a pulmonary specialist. Based on the World Health Organization (WHO) report that every year 4 out of 13 million deaths in developing countries are caused by respiratory tract infections, and at Dr. JH Awaloei Hospital, respiratory tract infections are ranked 4th out of 10 most common diseases. ARI can be treated with antibiotics if the microorganisms that cause it are bacteria, but the use of antibiotics must be in accordance with antibiogram data, rational and appropriate doses to prevent an increase in antibiotic resistance, because antibiotic resistance has become a chronic and global public health problem. Purpose: This study aims to identify aerobic bacterial patterns and antibiotic sensitivity tests in sputum samples of inpatients at Dr. J.H Awaloei Hospital. Methods: This study used a descriptive method with a cross sectional approach, namely by conducting bacterial pattern research on 15 samples, then cultured using nutrient agar and mac conkey at the Microbiology Laboratory of the Faculty of Medicine, Sam Ratulangi University. Results: Identification of bacteria by Gram staining. Antibiotic sensitivity test. The results of this study obtained Staphylococcus sp. (86.67%); Staphylococcus aureus (6.67%); Streptococcus sp. (6.67%). All bacteria were sensitive to the antibiotic Amikacin and resistant to Ampicillin and Clindamicin. The conclusion of this study is that the most bacteria found are Staphylococcus sp. which is most sensitive to Amikacin, Meropenem and most resistant to Ampicillin, Aztreonam, Clindamicin, Erythromycin.